2021
DOI: 10.1002/jgm.3329
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hsa_circ_0003489 shifts balance from autophagy to apoptosis and sensitizes multiple myeloma cells to bortezomib via miR‐874‐3p/HDAC1 axis

Abstract: Background: Circular RNAs (circRNAs) crucially regulate tumor progression. In this study, we examined the functional roles and mechanisms of hsa_circ_0003489 in multiple myeloma (MM).Methods: Upon altering the expressions of hsa_circ_0003489, miR-874-3p, and/or histone deacetylase 1 (HDAC1) in MM1.R cells and treating them with bortezomib (BTZ), cell viability was examined by CCK-8 assay; cell proliferation by Ki-67 immunofluorescence; apoptosis by TUNEL staining, flow cytometry, and western blot; and autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In parallel, circRERE was upregulated in BTZ-resistant MM samples and cells, and it positively regulated CD47 by sponging miR-152-3p, facilitating the resistance of MM to BTZ ( Fang et al, 2021 ). Recently, Tian et al ( Tian et al, 2021 ) found that silencing of circ_0003489 sensitized MM cells to BTZ in vitro and in vivo experiments. In-depth study unveiled that circ_0003489 sponged miR-874-3p and positively regulated its target protein, HDAC1, therefore attenuating the cytotoxic effects of BTZ in MM cells and reversing its inhibiting effect on autophagy ( Tian et al, 2021 ).…”
Section: Circrnas In MMmentioning
confidence: 99%
“…In parallel, circRERE was upregulated in BTZ-resistant MM samples and cells, and it positively regulated CD47 by sponging miR-152-3p, facilitating the resistance of MM to BTZ ( Fang et al, 2021 ). Recently, Tian et al ( Tian et al, 2021 ) found that silencing of circ_0003489 sensitized MM cells to BTZ in vitro and in vivo experiments. In-depth study unveiled that circ_0003489 sponged miR-874-3p and positively regulated its target protein, HDAC1, therefore attenuating the cytotoxic effects of BTZ in MM cells and reversing its inhibiting effect on autophagy ( Tian et al, 2021 ).…”
Section: Circrnas In MMmentioning
confidence: 99%
“…As shown in Table 1 , miR-874 is downregulated in at least 22 human malignancies, such as colorectal cancer (CRC) ( Huang et al, 2020a ; Yu et al, 2020 ; Que et al, 2017 ; Zhao and Dong, 2016 ; Han et al, 2016 ; Wang et al, 2021 ; Zhang et al, 2021c ), gastric cancer (GC) ( Huang et al, 2018 ; Sun et al, 2020 ; Yuan et al, 2020 ; Liu et al, 2017 ; Zhang et al, 2015 ; Jiang et al, 2014 ), hepatocellular carcinoma (HCC) ( Zhang et al, 2018b ; Jiang et al, 2017 ; Leong et al, 2017 ; Song et al, 2016 ), esophageal squamous cell carcinoma (ESCC) ( Yuan et al, 2018 ), pancreatic ductal adenocarcinoma (PDAC) ( Diao et al, 2018 ), non-small cell lung cancer (NSCLC) ( Bu et al, 2020 ; Yang et al, 2017 ; Ahmad et al, 2015 ; Kesanakurti et al, 2013 ; Wang et al, 2020b ), osteosarcoma (OS) ( Tang et al, 2018 ; Liu et al, 2020 ; Dong et al, 2016 ; Ghosh et al, 2017 ), epithelial ovarian cancer (EOC) ( Xia et al, 2018 ) cervical cancer (CC) ( Liao et al, 2018 ; Liu et al, 2021a ), retinoblastoma (RB) ( Zhang et al, 2018a ; Wang et al, 2020a ), prostate cancer (PCa) ( Pashaei et al, 2017 ) maxillary sinus squamous cell carcinoma (MSCC) ( Nohata et al, 2011 ), breast cancer (BC) ( Li et al, 2020 ; Zhang et al, 2017 ; Wang et al, 2014 ), triple-negative breast cancer (TNBC) ( Wu et al, 2020 ), rhabdomyosarcoma (RMS) ( Shang et al, 2019 ), papillary thyroid carcinoma (PTC) ( Ding et al, 2021 ), endometrial cancer ( Witek et al, 2021 ), cholangiocarcinoma ( Pan et al, 2021 ), glioma ( Li et al, 2021a ), myeloma (MM) ( Tian et al, 2021 ), head and neck squamous cell carcinoma (HNSCC) ( Nohata et al, 2013 ) and acute myeloid leukemia (AML) ( Zhang et al, 2021a ).…”
Section: The Aberrant Expression Of Mir-874 In Human Diseasesmentioning
confidence: 99%
“…In AML, the DANCR/miR-874-3p/ATG16L1 axis can promote autophagy, thereby enhancing the resistance of human AML cells to Ara-C ( Zhang et al, 2021a ). In addition, knocking out circ_0003489 can upregulate miR-874-3p and inhibit HDAC1, thereby prompting MM cells to switch from autophagy to apoptosis, and reducing the growth of MM cells ( Tian et al, 2021 ).…”
Section: The Effect Of Mir-874 On Prognosis and Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, cir-cANXA2 [74] was associated with chemoresistance of cytarabine and daunorubicin in AML. Similarly, circPAN3 [26] induced chemoresistance of adriamycin (ADM) via sponging miR-153-5p/miR-183-5p, while bortezomib (BTZ)-circ-0003489 [75] may regulate resistance in MM. Circ-0009910 triggered the activation of autophagy by sponging miR-34a-5p to promote imatinib resistance in chronic myeloid leukemia [68].…”
Section: Circrnas Influence Chemo-sensitivity In Hematological Malign...mentioning
confidence: 99%